Cancer as a risk factor for physical dysfunction and poor prognosis in patients with cardiovascular disease. (3rd October 2022) - Miki, T; Kamiya, K; Hamazaki, N; Nozaki, K; Ichikawa, T; Yamashita, M; Uchida, S; Noda, T; Ueno, K; Yamaoka-Tojo, M; Maekawa, E; Sasaki, J; et al.
Abstract: Introduction: The emerging interdisciplinary field of cardio-oncology is of interest to clinicians because a history of cancer or cancer treatment is considered a severe risk factor for cardiovascular disease (CVD). Both cancer and CVD can reduce skeletal muscle mass; together, they can lead to a poorer prognosis. However, it is unclear whether a patient's cancer history can lower physical function and lead to a poor prognosis with the coexistence of cancer history and physical dysfunction in patients with CVD. This study aimed to identify the relationship between cancer history and physical function, as well as the prognostic value of their combination, in patients with CVD. Methods: We reviewed 3, 640 patients with CVD (mean age, 67.9±13.5 years) who underwent physical-function tests (gait speed and 6-min walking distance [6MWD]). We performed multivariate linear regression analysis to assess potential associations between cancer history and physical-function tests in patients with CVD. Additionally, we used the Kaplan–Meier curve and Cox regression analyses to assess survival and prognostic significance for patients divided into four groups according to the presence or absence of cancer history and high or low physical function. Results: In multivariate linear regression analysis, cancer history was independently associated with lower gait speed and 6MWD (gait speed, P=0.048 and 6MWD, P=0.040). A total of 581 deaths occurred over a median follow-up period of 3.08 years (interquartile range: 1.36–5.27). For all-cause mortality, patients with a history of cancer and reduced physical function were found to have a significantly higher mortality risk even after adjusting for several covariates (gait speed, HR: 1.66, P=0.003 and 6MWD, HR: 1.71, P=0.003). Conclusion: Cancer history was correlated with physical dysfunction in patients with CVD. Moreover, the coexistence of cancer history and physical dysfunction resulted in poorer prognosis in patients with CVD. Funding Acknowledgement: Type of funding sources: None.